Impact of COVID-19 pandemic on medical school academic calendar: a dean's perspective (Journal of Patan Academy of Health Sciences, 2020)
Addressing the questions from students, faculties and students' parents regarding the academic calendar had become a part of my daily routine since the beginning of this COVID-19 pandemic. The online classes with pending practical and clinical teachings along with the questionable authenticity of the online exams of the undergraduate medical students and the compromised clinical teaching-learning of the postgraduate Residents with very few non-COVID patients in the hospital, stressed faculties, and the risk of infection requiring isolation, quarantine or admission has posed several questions regarding the academic calendar. How to adjust and reschedule the calendar, without compromising the course objectives and not losing the academic year, has become a challenge to medical schools and the leadership during this ongoing pandemic.